Response Surface Method for optimizing the injection moulding process in bracket production - Yusraini Muharni; Evi Febianti; Muhammad Galih Permana; Hartono Hartono (Universitas Sultan Ageng Tirtayasa, 2022)
Citra Karya Metal is a mould maker and injection service for industries that produce plastic products such as brackets for washing machines. Defective products in the bracket's production are serious problems since the number is large. The existence of this defective product is quite challenging for the company in terms of time and cost. Products that do not comply with the standards will be reworked by flushing them from excessive plastic or destroying them to become plastic pellets for rework. This research aims to provide recommendations for the optimum injection moulding machine settings to reduce defects in bracket production. The Response Surface Method is used to optimize three independent variables: injection speed, pressure, and screw backstop position. The research finds that the most influential factors were injection speed and pressure. The optimum factor level values for injection speed and pressure were 47.5 per cent and 61.5 bar, respectively.